Digital Fluency: Why Gamers Might Make Better Communicators - Suciana Wijirahayu; Eko Digdoyo; Retno Hendryanti; Asyam Ahmad Fathin (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose The primary objective of this study is to investigate how social media and online games influence student-lecturer interpersonal communication within a campus environment. Additionally, the research aims to identify strategies to mitigate adverse outcomes, such as potential addiction, while leveraging the positive benefits of these platforms to foster stronger academic relationships and English proficiency. Method This research employed a qualitative approach involving 70 Communication Science students in South Jakarta. Data were collected using a combination of semi-structured interviews and 20-item demographic questionnaires. The gathered data were then descriptively analyzed to understand the students' usage patterns and the subsequent impact on their academic communication and social interactions. Results/findings The study found that online games significantly enhance English speaking, pronunciation, and listening-based vocabulary through immersive, interactive environments. Furthermore, social media was shown to improve interaction with peers and lecturers by facilitating collaborative learning and direct engagement, effectively boosting students' confidence in English interpersonal communication. Conclusion These findings highlight the dual nature of digital tools, emphasizing their potential as educational aids despite the challenges of overuse. It is recommended that educators and policymakers develop balanced strategies and informed policies that maximize these linguistic and social benefits while mitigating potential drawbacks to ensure a healthy academic environment.